Study of Panchayati Raj in Independent India: Empowering Women through Panchayati Raj in Independent India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Panchayati Raj has been seen to be one of the main tools for catapulting women into active leadership in the decision-making phase in the administration of local authorities. Women's presence in local councils has brought numerous positive developments and has certainly boosted democracy at the grassroots level. In the Indian scenario, for women, who make up fifty per cent of the population, the local government, especially the administration at the traditional village level panchayats, was almost out of bounds. For decades, the voice of women in the decision-making phase of the municipal bodies was almost negligible or null. This paper reflect study of Panchayati Raj in Independent India